Konstruksi Visibilitas dalam Ekonomi Kreatif Pinggiran: Tinjauan Komunikasi atas Batik Kei di Kepulauan Kei - Ongirwalu, Maria Nathasya; Lestaluhu, Said (Universitas Pattimura, 2022)
This article examines the construction of visibility within peripheral creative economies through a case study of Batik Kei in the Kei Islands, Southeast Maluku. The study aims to understand how local creative actors establish cultural and economic presence through communicative strategies that are adaptive to social structures, geographic constraints, and local cultural values. Employing a descriptive qualitative approach, data were collected via in-depth interviews with the business owners of D.E Batik Kei, marketing personnel, employees, local government representatives, and consumers. Findings reveal that although the enterprise has implemented integrated marketing communication principles—including direct marketing, sales promotion, personal selling, public relations, and advertising—the strategies remain suboptimal. Limited human resources and low media engagement hinder consistent visibility and restrict broader market penetration. This study contributes to the sociology of communication by reframing visibility as a product of symbolic negotiation rather than mere promotional activity. It advocates for culturally grounded communication strategies and stronger engagement with local actors to strengthen peripheral creative economies as integral components of the national economic ecosystem. As such, the study offers both conceptual and practical insights at the intersection of communication, local culture, and creative industries.